The northeastern end of the Dunnage Zone in Newfoundland - Currie, Kenneth (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1995)
The northeastern end of the Dunnage Zone comprises the Notre Dame Subzone, bounded to the southeast by the Red Indian Line, and the Exploits Subzone bounded to the southeast by the GRUB Line, the boundary of the Dunnage Zone against the Gander Zone. The Notre Dame Subzone consists of diverse, fault-bounded assemblages of Arenig and older rocks unplaced in oceanic settings. The Exploits Subzone includes four fault-bounded belts distinguished by their Silurian stratigraphies (Badger, Botwood, Duder [new] and Indian Islands belts). All exhibit Ashgill-Llandovery, southeast-vergent sinistral thrusting which emplaced a fragment of the Botwood Belt on the Indian Islands Belt. Progressive post-Wenlock Silurian deformation produced dcxtral faults and upright folds east of the Dog Bay Line, a Silurian terrane boundary, whereas west of the line it produced northwest-vergent folds. Late Silurian to Devonian brittle sinistral motion modified the Red Indian and GRUB lines. Structural and stratigraphic observations suggest early Arenig obduction of the margin of the Exploits Subzone onto the Gander Zone followed by eastward subduction of old ocean crust (Notre Dame Subzone), along the Red Indian Line, produced a west-facing volcanic arc. Arc rifting in late Arenig time produced an active back-arc basin. Rapid basin filling and structural inversion, accompanied by eastward thrusting began in Ashgill time, probably due to arrival of Laurentia at the subduction zone. Remnants of the back-arc basin were closed by westward subduction in Llandovery and Wen lock time. Continent-continent contact, accompanied by further compression and extrusion of wedge-shape fragments between conjugate faults, occurred in late Silurian time.